Transcultural transformation in cinema - Yu. V. Vorontsova (Вестник университета)
The article presents a study of transcultural transformation in cinema, considering the filmmaker as a transnational figure. This is the gradual creation of a cinematic map based on affinitive transnationalism, which integrates forms of expression that are now considered archetypal. Members of the “imagined” cultural community construct a mosaic of shared references that transcend national boundaries. Based on this concept, a study of the organisational practices of filmmaker Carlos Saura has been conducted. This concept was the basis for a study of the organisational practices of director Carlos Saura, who in his last phase of his career focused on making films that offer samples of music, dance and unusual storytelling (based on the principle of “photography”) associated to the Iberian and Latin American space. This creates a special definition of the musical and artistic genres, combining traces of a documentary style influencing the authenticity of the representations depicted, with a strong aesthetic impulse emphasising the organisational and artistic nature of these representations. This model of transnationalism takes the form of reflection of trans-Iberian dimensions.